Stocks, bonds, money markets and exchange rates: measuring international financial transmission - Michael Ehrmann; Marcel Fratzscher; Roberto Rigobon (European Central Bank (ECB), 2005)
The paper presents a framework for analyzing the degree of financial transmission between money, bond and equity markets and exchange rates within and between the United States and the euro area. We find that asset prices react strongest to other domestic asset price shocks, and that there are also substantial international spillovers, both within and across asset classes. The results underline the dominance of US markets as the main driver of global financial markets: US financial markets explain, on average, more than 25% of movements in euro area financial markets, whereas euro area markets account only for about 8% of US asset price changes. The international propagation of shocks is strengthened in times of recession, and has most likely changed in recent years: prior to EMU, the paper finds smaller international spillovers.
Keywords: E44; F3; C5; 330; financial market linkages; integration; international financial markets; transmission; Internationaler Finanzmarkt; Spillover-Effekt; USA; EU-Staaten